Effectiveness of Auricular Acupressure Combined with Medication and Medical Advice for Smoking Cessation - Sivapornpun, Varaporn; Eamlaorsuk, Mareeya; Junyapoon, Suwannee (My University, 2024)
Materials and Methods: Two hundred eighty-two patients voluntarily participated in a smoking cessation program at the Smart Quit Clinic, Charoenkrung Pracharak Hospital. The patients were randomly divided into two groups, the treatment group (n=141) receiving specific auricular acupressure and the control group (n=141) receiving non-specific auricular acupressure. Five specific auricular acupressure points, including shenmen, lung, mouth, stomach, and sympathetic, were used to treat NWS. Each point was pressed with Wang Bu Liu Xing for one minute. The acupressure was applied three times a day for 12 weeks. The succession of cessation was assessed using carbon monoxide (CO) levels in exhaled breath and relief of NWS.Objective: Nicotine withdrawal symptoms (NWS) are the main impediments to the quitting attempt. The present study investigated the effectiveness of specific auricular acupressure combined with medication and medical advice to quit smoking.Results: The success of smoking cessation in the treatment group was significantly higher than the control group after cessation at weeks 12 and 24. Specific auricular acupressure such as shenmen, lung, mouth, stomach, and sympathetic, could reduce anxiety, craving on smoking, insomnia, and nervous symptoms since the first week after cessation.Conclusion: Specific auricular acupressure using Wang Bu Liu Xing is an effective and safe treatment method for relieving NWS.
Keywords: Auricular acupressure; Nicotine withdrawal symptoms (NWS); Smoking cessation; Wang Bu Liu Xing